Geoestatística e atributos do solo em áreas cultivadas com cana-de-açúcar - de Souza, Zigomar Menezes; Marques Jr., José [UNESP]; Pereira, Gener Tadeu [UNESP] (My University, 2010)
The intense traffic of agricultural machines in soils cultivated with sugar cane can cause soil compaction. Therefore, the objective of this research was to characterize the spatial variability of soil physical attributes and content organic matter of a eutroferric Red Latosol gibbisitic (under Basalt) and dystroferric Red Latosol caulinitic (under Sandstone) in the depths of 0.0-0.2m and 0.2-0.4m in areas cultivated with sugar cane. Soils were sampled at the crossing points of a grid at regular intervals of 10m and at depths of 0.0-0.2m and 0.2-0.4m. Bulk density, macroporosity, organic matter content and soil penetration resistance were measured for all sampling points. The physical attributes show values of soil penetration resistance, bulk density and macroporosity above average for these soils. The studied variable presented a larger range and minor variation coefficient in the eutroferric Red Latosol (Oxisol Eutrustox) when compared with the dystroferric Red Latosol (Oxisol Haplustox), in the studied depths. It is recommended a bigger number of samples to study the eutroferric Red Latosol attributes and the depth of 0.2-0.4m.
Geostatistics and soil attributes in area cultivated with sugar cane
Keywords: Oxisol; Saccharum offcinarum; Spatial variability